Service Agreement as a type of obligation (Journal of actual problems of jurisprudence, 2019)
In the contract on rendering of services obligations occurs and is formed by the contract of compensated rendering of services. As a rule, the contract of civil paid services is a new type of contract in civil law, which is referred to in article 683 of the Civil code of the Republic of Kazakhstan. Terms of paid services include: telecommunications, medical services, veterinary medicine, audit, consulting, advertising, information, educational services, travel services, etc.in accordance with the agreement on paid services, the contractor undertakes to provide services on behalf of the customer, that is, to take certain actions or perform certain actions, and the customer undertakes to pay for it. Fees paid for these services under Soviet law are recognized as illegal profits and are not supported by the state. Legal support was provided when these services were transferred to the new economic relations and after the adoption of the Special part of the joint service of Kazakhstan. Depending on the nature of the adjustment, these terms are set out in the contract terms and conditions of service.In the future, taking into account the stable development of the market of services, it can be assumed that the service contract in the future will be one of the most popular and dynamically developingcivil law institutions.Key words: services, paid services, obligation, contractor, customer, contract.